1997
DOI: 10.1159/000268001
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanism of Exacerbating Cataract Formation in Cataractous Human Lens Capsules Induced by Systemic Hypertension or Glaucoma

Abstract: To clarify the role of the lens capsule in cataract formation, changes in the protein conformational structure of immature cataractous lens capsules from patients with systemic hypertension or glaucoma have been investigated, as compared to normal lens capsules. The protein secondary structure and composition of these capsular samples were determined using Fourier transform infrared microspectroscopy with second-derivative, deconvolution and curve-fitting methods. We found that the composition of both random c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 23 publications
1
29
0
1
Order By: Relevance
“…Only a few studies have provided evidence that the amyloid misfolding pathway may be physiologically relevant. For example, FTIR spectra of decapsulated cataract tissue exhibits an absorption at 1620 cm −1 , which is especially pronounced in cataract tissue taken from patients that suffer from glaucoma (77). This amide I frequency indicative of the extended vibrational coupling in amyloid β-sheets (Table 1) (49, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have provided evidence that the amyloid misfolding pathway may be physiologically relevant. For example, FTIR spectra of decapsulated cataract tissue exhibits an absorption at 1620 cm −1 , which is especially pronounced in cataract tissue taken from patients that suffer from glaucoma (77). This amide I frequency indicative of the extended vibrational coupling in amyloid β-sheets (Table 1) (49, 51).…”
Section: Discussionmentioning
confidence: 99%
“…To date, amyloid fibers have not been observed in protein aggregates taken from cataractous lenses, despite the apparent high propensity for crystallins to form amyloid fibers in vitro . However, in a few cases where the infrared spectra of such aggregates have been measured, low‐frequency absorption near 1620 cm −1 , which is characteristic of extended amyloid β‐sheets, have been reported . The fact that such spectral features are observed for aggregates that form sheets instead of fibers indicates that amyloid‐like aggregation may occur even where fibers are not observed.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,[11][12][13][14][15][16]20,25,73 However, in a few cases where the infrared spectra of such aggregates have been measured, lowfrequency absorption near 1620 cm 21 , which is characteristic of extended amyloid b-sheets, have been reported. 74 The fact that such spectral features are observed for aggregates that form sheets instead of fibers indicates that amyloid-like aggregation may occur even where fibers are not observed. In fact, amyloid-like infrared spectra of g-crystallins, without the presence of fiber morphology in TEM images, has been observed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IOP is the most crucial risk factor for glaucoma, and a sufficiently high IOP level can cause ocular tissue damage [7,8]. The study has reported that systemic hypertension or glaucoma might change the protein secondary structures of the immature cataractous lens capsule and alter ionic transport through the deformed lens capsule [9]. Therefore, protein expression alterations in various intraocular tissues, including the cornea, conjunctiva, uvea (composed of the iris, ciliary body, and choroid), retina, and sclera, during ischemia–reperfusion (IR) injury, may play a crucial role in clinical ophthalmology.…”
Section: Introductionmentioning
confidence: 99%